Efektivitas Kerjasama Open Library Telkom University dengan Universidade Da Paz (Unpaz) Timor Leste dalam Bentuk E-Resources - Hasna Yunita; Prijana Prijana (Jurnal Pustaka Ilmiah, 2024)
This collaboration was carried out to help Universidade Da Paz (UNPAZ) Timor Leste obtain various sources of information from e-resources in the Open Library Telkom University. The formulation of the problem in this research is 1) what is the form of collaboration between the Open Library Telkom University and UNPAZ 2) What is the impact and effectiveness of the collaboration between Open Library Telkom University and UNPAZ in accessing e-resources 3) What were the obstacles faced when this collaboration was carried out by the Open Library Telkom University and UNPAZ. Apart from that, to find out the impact and effectiveness of this collaboration. Lastly, to find out the problems faced when this collaboration in accessing e-resources takes place. The research method used is qualitative research through interviews, observation, and literature review. The results of the discussion in this research are a collaboration between Open Library Telkom University and UNPAZ in the form of accessing e-resources. Apart from that, this collaboration has a positive impact on both parties, and the obstacles faced when carrying out this collaboration are network constraints, language differences, and very minimal knowledge about how to use e-resources. The suggestion is to learn the languages used by each other, both from the Open Library Telkom University and the UNPAZ. Apart from that, improving internet network facilities for UNPAZ.